PENGARUH COMPUTER ANXIETY DAN TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP TECHNOSTRESS PADA GURU SMK DI KABUPATEN KARANGANYAR - Effiyanti, Tri; M.Stats, Siswandari; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2014)
The research objective was to determine: 1) the influence of computer anxiety to the TAM, 2) TAM effect on work overload, 3) the influence of computer anxiety against job insecurity, 4) effect of work overload and job insecurityto technostress of teacher in SMK Karanganyar. This research is quantitative survey methods. The study population was all vocational teachers SMK Karanganyar Business and Management. The research sample was taken as the population by purposive sampling technique. Data collection techniques used were observation and questionnaires. Techniques of data analysis done with path analysis. Results of this study are as follows: 1) computer anxiety significantly affects the TAM, 2) TAM significant part of affects the work overload, 3) computer anxiety effect is not significant to job insecurity, 4) work overload and job insecurity significant part of affects technostress vocational teachers in SMK Karanganyar, 5) directly, technostress influenced by the work overload and job insecurity by 58%, 6) effective overall contribution models is 83%.Keywords: Computer Anxiety, Technology Acceptance Model (TAM),Technostress